Igbo historiography: Part II - Chuku, Gloria (History compass, 2018)
Igbo historiography has advanced since the publication of the epic narrative of Olaudah Equiano in 1789 and its different versions, especially that of Paul Edwards, a British literary historian in 1969. The main objective of this essay is to demonstrate the vitality and diversity of Igbo historical studies and provide informative and thoughtful interpretations of its strengths and weaknesses. In three parts, the essay examines the origin, dispersal, and settlement of the people; sociopolitical institutions and organization; economic systems, including slavery and the transatlantic slave trade, and the colonial economy; Igbo religion, Islam, Christianity, and Western education; colonial encounter; the Igbo in precolonial and modern Nigeria with focus on intergroup relations, ethnicity, and the Nigeria-Biafra War; and Igbo intellectual history. The essay makes a spirited critique of areas of overemphasis and the conceptual and methodological issues. It suggests important neglected themes that require further historical investigations. Its primary goal is to nudge Igbo historiography in new and challenging directions and inspire historians interested in Igbo studies to adopt a historiographical approach that emphasizes currency, relevance, and usability.